A Shunt Active Power Filter Based on Instantaneous Reactive Power Compensation and Direct Voltage Control for Medium-Voltage Applications - Krishnaveni, V.; Kalyan, C. Pavan (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
High power and medium voltage (MV) applications need Controlled rectifiers such as 12-pulse converters, because of the high reliability, low complexity, robustness and low power losses. But having the drawback of harmonics generation causes power quality problem. Power quality can be improved with passive filters but having disadvantages such as dependency on the source impedances, parallel and series resonance, aging of passive components. Active power filtering (APF) is used as compensation technique in order to improve thepower quality at the line side. Hence APF becomes a promising compensator solution. This paper presents the APF for a Medium-Voltage applications using Open Loop Control Compensation.